2020
DOI: 10.31234/osf.io/2a9zm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Six of one, half dozen of the other: Suboptimal prioritizing for equal and unequal alternatives

Abstract: When presented with two difficult tasks and limited resources, it is better to focus on one task and complete it successfully than to divide your efforts and fail on both. Although this logic seems obvious, people demonstrate a surprising failure to apply it when faced with prioritizing dilemmas. In previous research, the choice about which task to prioritise was arbitrary, because both tasks were equally difficult and had the same reward for success. In a series of three experiments, we investigated whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…To foreshadow the results, in Experiment 1 of the current report, we implemented the fire trucks task and found that unlike previous versions of the focus-divide dilemma (e.g., Clarke & Hunt, 2016 ; James et al, 2017 ; James et al, 2019 ; James et al, 2023 ; Morvan & Maloney, 2012 ), participants made choices that were closer to optimal. For the investigation of individual differences that was our original motivation, this is a limitation because participants are more uniform by virtue of being closer to optimal.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…To foreshadow the results, in Experiment 1 of the current report, we implemented the fire trucks task and found that unlike previous versions of the focus-divide dilemma (e.g., Clarke & Hunt, 2016 ; James et al, 2017 ; James et al, 2019 ; James et al, 2023 ; Morvan & Maloney, 2012 ), participants made choices that were closer to optimal. For the investigation of individual differences that was our original motivation, this is a limitation because participants are more uniform by virtue of being closer to optimal.…”
Section: Introductionmentioning
confidence: 70%
“…The sample size for this experiment was based on a power analysis as described by James and colleagues ( 2023 ). They used bootstrapping methods from previously collected focus-divide task datasets to simulate a small shift in position choices (0.05 of the normalised range) at different sample sizes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations